Pengaruh Implantasi Hormon LHRH-A terhadap Perkembangan Gonad Kerapu Bebek, Cromileptes altivelis - Tridjoko Tridjoko (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The purpose of this experiment was to know the effect of implantation LHRH-a hormone on gonade maturation of grouper Cromileptes altivelis. The weight of female broodfishes were used between 1.40 and 1.65 kg/pcs and total lenght between 41.0 and 48.0 cm. Some of 5 fishes were stocked into the 75 m3 circular concrete tank. The treatment was implanted hormone LHRH-a i.e.: (A) 3 times; (B) 1 time; and (C) no implant. The results of the experiment showed that the effect of LHRH-a hormone implanted was significantly different (P